Kewenangan Daerah dalam Pengelola Keuangan Berdasarkan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Surahman, Adi; Suryaningsi, Suryaningsi; Rosmini, Rosmini (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
In carrying out regional financial management and how the duties of regional financial management officials Legal arrangements regarding regional state financial management powers are based on the Law of the Republic of Indonesia Number 17 of 2003 concerning State Finance and Law of the Republic of Indonesia Number 23 of 2014 concerning Regional Government. The President as the Head of Government holds the power of state financial management as part of government power. The power to manage State finances includes general authority and special authority and the regional head is the holder of regional financial management power which in its implementation the regional head delegates part or all of its powers in the form of planning, implementation, administration, reporting and accountability, and supervision of regional finances to regional apparatus officials based on the principle of separation of authority between those who order, test, and those who receive/issue money.